Spectra of the extended neighborhood corona and extended corona of two graphs - Chandrashekar Adiga; Rakshith B.R.; Subba Krishna K.N. (Electronic Journal of Graph Theory and Applications (EJGTA), 2016)
In this paper we define extended corona and extended neighborhoodcorona of two graphs $G_{1}$ and $G_{2}$, which are denoted by$G_{1}\bullet G_{2}$ and $G_{1}* G_{2}$ respectively. Wecompute their adjacency spectrum, Laplacian spectrum and signlessLaplacian spectrum. As applications, we give methods to constructinfinite families of integral graphs, Laplacian integral graphsand expander graphs from known ones.